LungBEAM: A prospective multicenter study to monitor stage IV NSCLC patients with EGFR mutations using BEAMing technology. (23rd July 2021) - Garrido, Pilar; Paz‐Ares, Luis; Majem, Margarita; Morán, Teresa; Trigo, José Manuel; Bosch‐Barrera, Joaquim; Garcίa‐Campelo, Rosario; González‐Larriba, José Luis; Sánchez‐Torres, José Miguel; Isla, Dolores; Viñolas, Núria; Camps, Carlos; et al.
Abstract: Objectives: The aim of LungBEAM was to determine the value of a novel epidermal growth factor receptor ( EGFR ) mutation test in blood based on BEAMing technology to predict disease progression in advanced non‐small cell lung cancer (NSCLC) patients treated with first‐ or second‐generation EGFR‐tyrosine kinase inhibitors (EGFR‐TKIs). Another goal was to monitor the dynamics of EGFR mutations, as well as to track EGFR exon 20 p.T790M (p.T790M) resistance during treatment, as critical indicators of therapeutic efficacy and patient survival. Methods: Stage IV NSCLC patients with locally confirmed EGFR‐TKI sensitizing mutations (ex19del and/or L858R) in biopsy tissue who were candidates to receive first‐ or second‐generation EGFR‐TKI as first‐line therapy were included. Plasma samples were obtained at baseline and every 4 weeks during treatment until a progression‐free survival (PFS) event or until study completion (72‐week follow‐up). The mutant allele fraction (MAF) was determined for each identified mutation using BEAMing. Results: A total of 68 of the 110 (61.8%) patients experienced a PFS event. Twenty‐six patients (23.6%) presented with an emergent p.T790M mutation in plasma at some point during follow‐up, preceding radiologic progression with a median of 76 (interquartile ratio: 54–111) days. Disease progression correlated with the appearance of p.T790M in plasma with a hazard ratio (HR) of 1.94 (95% confidence interval [CI], 1.48–2.54; p  < 0.001). The HR for progression in patients showing increasing plasma sensitizing mutation levels (positive MAF slope) versus patients showing either decreasing or unchanged plasma mutation levels (negative or null MAF slopes) was 3.85 (95% CI, 2.01–7.36; p  < 0.001). Conclusion: Detection and quantification of EGFR mutations in circulating tumor DNA using the highly sensitive BEAMing method should greatly assist in optimizing treatment decisions for advanced NSCLC patients. Abstract : The manuscript is a multicenter, prospective study conducted in the real‐world setting. The study reveals that the detection and quantification (MAF slope) of EGFR mutations in ctDNA using the highly sensitive BEAMing method may assist in optimizing treatment decisions for advanced NSCLC patients.